Isolation, Identification and Characterization of AZO Dye reactive Violet 5R Degrading Bacterial Strains from the Textile Sludge - Siddique, Romana; Ahmed, Hasan Hasnaeen (Journal of Bangladesh Academy of Sciences, 2018)
Three bacterial strains, Streptococcus equi subsp. zooepidemicus, Brevibacillus centrosporus and Paenibacillus azoreducens, have been isolated from the sludge samples collected from Textile Industry, Bhaluka, Bangladesh, which have the abilities to degrade Reactive Violet 5R. The decolourization rate was different for the different concentrations of the same dye. Brevibacillus centrosporus displayed a decolorization rate of 94.55%, 90.79%, 91.17% when inoculated and incubated in an SM broth containing the azo dye reactive violet 5R at 1% (v/v), 3% (v/v) and 5% (v/v) concentrations respectively for a consecutive 5 days. Paenibacillus azoreducens showed a decolorization rate of 85.63%, 86.48%, 38.81% for the 1% (v/v), 3% (v/v), and 5% (v/v) of the azo dye reactive violet 5R respective concentrations. On the other hand Streptococcus equi subsp zooepidemicus produced intriguing results where the decolorization rates were 67.78%, 21.69%, 40.10% for 1% (v/v), 3% (v/v) and 5% (v/v) respectively of the azo dye reactive violet 5R. Journal of Bangladesh Academy of Sciences, Vol. 41, No. 2, 136-143, 2017